Specialized Tourism Management and Its Effects on Improving Hotel Services - Instructor Dr. Jaafar Imran Mohammed Saeed (Peerian Journals Publishing, 2024)
The current research paper aims to provide a new type of hotel service that seeks to provide a comprehensive specialized management to all tourism organizations in general and hotel organizations in particular. This type of management is trained and prepared to provide accurate and urgent information and guidance. The research problem comes through posing the following question: What is the relationship of specialized management in improving hotel service? This pattern is one of the easy and simple patterns that is capable of understanding the requirements and needs of the tourist and the impact of services through specialized management. Planning, proper control and direct implementation achieve the required service that leads to the guest’s satisfaction. A number of questionnaire forms are distributed to (95) male and female tourists (guests and guests) and a group of managers (95) within a number of excellent and first-class hotels in the holy Karbala Governorate to achieve the research objectives which are intended to improve hotel service.
Keywords: specialized tourism management; improving hotel service